IL-2 Expression in Activated Human Memory FOXP3+ Cells Critically Depends on the Cellular Levels of FOXP3 as Well as of Four Transcription Factors of T Cell Activation - Bendfeldt, Hanna; Benary, Manuela; Scheel, Tobias; Steinbrink, Kerstin; Radbruch, Andreas; Baumgrass, Ria (Frontiers in Immunology, 2012)
The human CD4+FOXP3+ T cell population is heterogeneous and consists of various subpopulations which remain poorly defined. Anergy and suppression are two main functional characteristics of FOXP3+Treg cells. We used the anergic behavior of FOXP3+Treg cells for a better discrimination and characterization of such subpopulations. We compared IL-2-expressing with IL-2-nonexpressing cells within the memory FOXP3+ T cell population. In contrast to IL-2 nonexpressing FOXP3+ cells, IL-2-expressing FOXP3+ cells exhibit intermediate characteristics of Treg and Th cells concerning the Treg cell markers CD25, GITR, and Helios. Besides lower levels of FOXP3, they also have higher levels of the transcription factors NFATc2, c-Fos, NF-Bp65, and c-Jun. An approach combining flow cytometric measurements with statistical interpretation for quantitative transcription factor analysis suggest that the physiological expression levels not only of FOXP3 but also of NFATc2, c-Jun, c-Fos, and NF-Bp65 are limiting for the decision whether IL-2 is expressed or not in activated peripheral human memory FOXP3+ cells. These findings demonstrate that concomitant high levels of NFATc2, c-Jun, c-Fos, and NF-Bp65 lead in addition to potential IL-2 expression in those FOXP3+ cells with low levels of FOXP3. We hypothesize that not only the level of FOXP3 expression but also the amounts of the four transcription factors studied represent determining factors for the anergic phenotype of FOXP3+ Treg cells.